PENGARUH SISTEM INFORMASI AKUNTANSI PEMBERIAN PINJAMAN BERGULIR TERHADAP PENINGKATAN KINERJA BKM KELURAHAN PANDANWANGI KOTA MALANG - Kristi, Bajeng Dika (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2014)
Accounting information system is needed because it can be used as a reference management in running the business. In order to create a good performance there must be an accurate accounting information system as an internal control in carrying out operational activities. With a system of good information and accurate accounting is expected to improve the performance particularly in the BKM Pandanwangi Malang that can still compete with the other competitors. The purpose of this study was to determine the effect of accounting information systems on the performance of revolving loan BKM Pandanwangi Malang. The sample in this study is the client or Kelompok Swadaya Masyarakat BKM Pandanwangi Malang using saturated samples are all members of the population used as a sample. Analysis using simple linear regression analysis. The results showed that the accounting information system revolving lending significant effect on the performance of the BKM Pandanwangi Malang. For further research of the results of this study are expected to be used as a reference in the literature or in conducting further research. Also expected to further research in order to add new variables corresponding to this research so that research result can grow better.